Resolving a dilemma of signaling bankrupt‐firm emergence: A dynamic integrative view - Xia, Jun; Dawley, David D.; Jiang, Han; Ma, Rong; Boal, Kimberly B. (Strategic Management Journal, 2016)
Research summary : Predicting the emergence of bankrupt firms relying on firm signals involves a stigma‐related dilemma. On the one hand, bankrupt firms tend to send positive signals through restructuring to decouple themselves from the stigma of bankruptcy. On the other hand, the preexistence of the bankruptcy stigma may reduce the signaling effectiveness of firms' restructuring efforts, making the outcome prediction difficult. We address this dilemma by developing a dynamic integrative view to extend signaling theory, arguing that subsequent signals from key external stakeholders can effectively help evaluate bankrupt firms' quality and reduce the ambiguity in interpreting firms' restructuring signals. Using a sample of U.S. public bankrupt firms under Chapter 11 reorganization, we find evidence supporting the argument. Managerial summary : Applications of signaling theory to predict reorganization outcomes are in their infancy. The dynamic integrative framework developed in this study is useful in identifying different types of signals and predicting outcomes of firms in crisis. The results of this study can be useful for various decision makers to predict the turnaround potential of bankrupt firms. Our results show that an increase in alliance partners, institutional investors, and securities analysts following a bankrupt firm predicts the firm's reorganization outcome. Moreover, firms that are able to gain positive attention from key stakeholders will also gain positive interpretations of their strategic efforts. Signals from alliance partners and institutional investors amplify the signaling effect of a firm's de‐diversification effort in predicting its reorganization outcome. Copyright © 2015 John Wiley & Sons, Ltd.